Pre-Roman and Roman Winchester. - Clarke, Giles, (Winchester studies ;, 2021)
Outside the north gate of Venta Belgarum, Roman Winchester, a great cemetary stretched for 500 yards along the road to Cirencester. Excavations at Lankhills from 1967 to 1972 uncovered 451 graves, many elaborately furnished, at the northern limits of this cemetery, and dating from the fourth century A.D. This book describes the excavations of these burials and analyses, in detail, both the graves and their contents. There are detailed studies and important re-assessments of many categories of object, but it is the information about late Roman burial, religion, and society which is of special interest.